Promotion of Bamboo Mosaic Virus Accumulation in Nicotiana benthamiana by 5′→3′ Exonuclease NbXRN4 - Lee, Cheng-Cheng; Lin, Tzu-Ling; Lin, Jhe-Wei; Han, Yu-Tsung; Huang, Yu-Ting; Hsu, Yau-Heiu; Meng, Menghsiao (Frontiers in Microbiology, 2016)
Bamboo mosaic virus (BaMV) has a 6.4-kb (+) sense RNA genome with a 5’ cap and a 3’ poly(A) tail. ORF1 of this potexvirus encodes a 155-kDa replication protein responsible for the viral RNA replication/transcription and 5’ cap formation. To learn more about the replication complex of BaMV, a protein preparation enriched in the 155-kDa replication protein was obtained from Nicotiana benthamiana by a protocol involving agroinfiltration and immunoprecipitation. Subsequent analysis by SDS-PAGE and mass spectrometry identified a handful of host proteins that may participate in the viral replication. Among them, the cytoplasmic exoribonuclease NbXRN4 particularly caught our attention. NbXRN4 has been shown to have an antiviral activity against Tomato bushy stunt virus and Tomato mosaic virus. In Arabidopsis, the enzyme could reduce RNAi- and miRNA-mediated RNA decay. This study found that downregulation of NbXRN4 greatly decreased BaMV accumulation, while overexpression of NbXRN4 resulted in an opposite effect. Mutations at the catalytically essential residues abolished the function of NbXRN4 in the increase of BaMV accumulation. Nonetheless, NbXRN4 was still able to promote BaMV accumulation in the presence of the RNA silencing suppressor P19. In summary, the replication efficiency of BaMV may be improved by the exoribonuclease activity of NbXRN4.